Globalization, violence, and the visual culture of cities - Lindner, Christoph (Questioning cities, 2010)
Globalization and violence / Christoph Lindner -- Architecture and economies of violence : São Paulo as case study / Richard J. Williams -- Drugs and assassins in the city of flows / Geoffrey Kantaris -- Temporary discomfort : Jules Spinatsch's documentation of global summits / Hugh Campbell -- American military imaginaries and Iraqi cities : the visual economies of globalizing war / Derek Gregory -- Globalization and the remembrance of violence : visual culture, space, and time in Berlin / Simon Ward -- Trash aesthetics : New York, globalization, and garbage / Christoph Lindner -- Global Beijing : the world is a violent place / Stephanie Hemelryk Donald -- The poetics of scale in urban photography / Shirley Jordan -- Globalization and cultural capital : symbolic violence in recent filmic images of Paris / Ruth Cruickshank -- Conspiracy, surveillance, and the spatial turn in the Bourne trilogy / Sue Harris